Weighing worth against uncertain work: the interplay of exhaustion, ambiguity, hope and disappointment in mothers breastfeeding late preterm infants. Issue 1 (1st October 2012) - Demirci, Jill Radtke; Happ, Mary Beth; Bogen, Debra L.; Albrecht, Susan A.; Cohen, Susan M.
Abstract: Poor breastfeeding outcomes among late preterm infants (LPIs) have been attributed to inadequate breast milk transfer stemming from physiological immaturities. However, breastfeeding is more than a biological phenomenon, and it is unclear how mothers of LPIs manage other factors that may also impact the breastfeeding course. Using grounded theory methods and incorporating serial post‐partum interviews with several novel data collection techniques, we examined breastfeeding establishment over a 6–8‐week‐period among 10 late preterm mother‐infant dyads recruited from a maternity hospital in Pittsburgh, Pennsylvania, USA. We found that breastfeeding in the LPI population was a fluctuating, cascade‐like progression of trial and error, influenced by a host of contextual factors and events and culminating with breastfeeding continuation (with or without future caveats for duration or exclusivity of breastfeeding) or cessation. The trajectory was explained by the basic psychosocial process Weighing Worth against Uncertain Work, which encompassed the tension among breastfeeding motivation, the intensity of breastfeeding work and the ambiguity surrounding infant behaviour and feeding cues. Several sub‐processes were also identified: Playing the Game, Letting Him be the Judge vs. Accommodating Both of Us and Questioning Worth vs. Holding out Hope . If valid, our theoretical model indicates a need for earlier, more extensive and more qualified breastfeeding support for mothers of LPIs that emphasizes the connection between prematurity and observed feeding behaviours.